2014
DOI: 10.5414/cn108258
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy in patients over 75: 131 cases

Abstract: Introduction: Demographic analysis shows the ageing of the global population and the consequent increase in the age of hospitalized subjects and of patients starting dialysis. Hence, interest in the feasibility, safety, and usefulness of renal biopsy in elderly patients is growing. We examined the data of 131 patients over the age of 75 who underwent renal biopsy. We analyzed the safety of the procedure, treatment, and outcomes. Results: Histological diagnoses included: membranous glomerulonephritis (GN) 20.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
1
6
0
8
Order By: Relevance
“…Studies in elderly patients in the United States showed similar findings of lacking significant increase in the procedurerelated complication rate, and in two-thirds of patients, treatment strategy was modified based on the biopsy findings. 4,5 Recent studies from Italy, 7 Spain, 18,19 Japan 20 and China 10,12 showed similar results of biopsy being valuable clinically for elderly patients.…”
Section: Pros and Cons Of Kidney Biopsy For Elderly Patientsmentioning
confidence: 87%
See 3 more Smart Citations
“…Studies in elderly patients in the United States showed similar findings of lacking significant increase in the procedurerelated complication rate, and in two-thirds of patients, treatment strategy was modified based on the biopsy findings. 4,5 Recent studies from Italy, 7 Spain, 18,19 Japan 20 and China 10,12 showed similar results of biopsy being valuable clinically for elderly patients.…”
Section: Pros and Cons Of Kidney Biopsy For Elderly Patientsmentioning
confidence: 87%
“…Based on publications from 2000 to the present, the occurrence rates in patients >60 or 65 years of age were 8-10% in China, 10-12,29~4 -7% in the United States 4,5 and 5-7% in Europe. 8,9,30 However, when age cut-off was set at >75 or ≥80 years, the occurrence rate rose to the range of 7-10.6% in patients from Europe 7,19 and the United States, 4 similar to the rate in Asia, 14 suggesting an increased occurrence of IgA nephropathy in the very elderly across geographical and ethnic backgrounds. The pathogenesis of primary IgA nephropathy is detailed in recent reviews.…”
Section: Iga Nephropathy In Elderly Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…Major side effects such as bleeding severe enough to require transfusion, vascular intervention, or nephrectomy are far rarer [11-14]. The few retrospective studies that have examined complication rates in the elderly (age >75 years) have reported low risk rates that do not differ from that of younger patients [15, 16]. One small prospective study comparing 26 patients >60 years of age with 184 younger subjects undergoing ultrasound-guided renal biopsy with a 16 gauge automated gun, reported a higher risk of gross hematuria post biopsy in the elderly group.…”
Section: Renal Biopsy In the Very Elderly (Over 80 Years Of Age)mentioning
confidence: 99%